Análisis, diseño e implementación de servicios en línea (detalles de llamadas, facturas y guía virtual) en linkotel s.a. - Saltos, Carlos (2009)
The project that is described in this document, has as principal aim develop 3 services on line in Linkotel S.A. to optimize time in the clients, under a basic scheme of safety of 3 layers, prosecuting as result to improve the times of answers the clients, reducing the losing portfolio and giving empowerment to client 24 hours of the day, 7 days of the week, about the information that him concerns by Internet.